The Effectiveness of the High Intensity Interval Training (HITT) Method on Increasing the Leg Muscle Power of Volleyball Players - Muhamad, Rizki Khofiudin Nur; Hariadi, Imam; Fadhli, Nurrul Riyad (Indonesian Journal of Sport Management, 2024)
The study aims to determine the effectiveness of the High Intensity Interval Training (HIIT) method on increasing the leg muscle power of male volleyball players in the Train to Train phase aged 12-16 years Active Movement Volleyball School. This research is a pre-experimental design using the One Group Pretest-Posttest design with a quantitative descriptive approach. The population in this study were Active Movement Volleyball School volleyball players. Sampling was carried out using Purposive sampling technique as many as 12 male Active Movement Volleyball School players aged 12-16 years. The instrument used is the vertical jump test to determine the ability of leg muscle power using jump MD. The pretest-posttest results of male volleyball players were 59.3 ± 7.47 ver. 64,6 ± 7,48. In the prerequisite test, there is a normality test using the shapiro-wilk technique and it is known that the pretest-posttest data is normally distributed with a significance value of 0.278 pretest and 0.499 posttest> 0.05. For the homogeneity test using the levene statistic technique, the vertical jump results have a homogeneous variant of 0.880> 0.05. Furthermore, hypothesis testing, using the paired sample t-test analysis technique on the results of the vertical jump test for male volleyball players obtained a value of 0.000 <0.05. From these results, it is known that there is a significant effect of the High Intensity Interval Training (HIIT) method on increasing the leg muscle power of volleyball players with an increase of 5.3. Based on the findings of the results, it is concluded that the High Intensity Interval Training (HIIT) method makes a significant contribution to increasing the leg muscle power of male volleyball players at Active Movement Volleyball School in the Train to Train phase where the experimental p hypothesis test value is obtained <0.05.